A high-reliability scan driver integrated circuit by MO TFTs for a foldable display. (27th February 2023) - Liu, Chun; Zhou, Lei; Zhou, Zhao-Hua; Li, Fei-Fan; Wei, Xiao-Qin; Xu, Miao; Wang, Lei; Wu, Wei-Jing; Peng, Jun-Biao
Abstract: Foldable displays have become increasingly used as a solution to the portability-practicality trade-off. A new scan driver integrated with metal oxide thin film transistors (MO TFTs) is proposed for foldable displays to overcome the effects of threshold voltage shifts on the scan driver output. In the scan driver, a feedback section and two series to transistor structures are used to keep the voltage of the key node to sustain a normal output, with this structure, the lower the voltage of the negative supply, the more stable the scan driver will be. Some flexible MO TFTs and 60 stage scan drivers are fabricated by etch stop layer structures on the polyimide substrate. Under different strains and 100 000 times bending with the minimum 3.5 mm bending radius, the characteristics of MO TFTs and the output waveform of the scan driver are measured. Experimental results show that the proposed scan driver shows high reliability since only a little voltage fluctuation occurs at the outputs after the bending test and has a better output waveform with a lower voltage of the negative supply.